EXPLORING SPATIAL REPRESENTATION-BASED LEARNING IN EFL DESCRIPTIVE WRITING: A QUALITATIVE CASE STUDY - Yulianti Sanusi; Ahmad Bukhori Muslim; Wawan Gunawan (Universitas Darussalam Gontor, 2026)
Writing descriptive texts remains a persistent challenge for English as a Foreign Language (EFL) learners, particularly in generating ideas and developing detailed written content. This study aimed to investigate the implementation of Spatial Representation-Based Learning (SRBL) in enhancing the descriptive writing skills of second-semester Hospitality students at Institut Citra Buana Indonesia. Employing a qualitative case study design, the research explored how SRBL facilitated students’ writing development through authentic environmental observation and structured descriptive activities. Data were collected through classroom observations, students’ writing products, and semi-structured interviews. Following the interactive analysis model of Miles, Huberman, and Saldaña (2020), the data were analysed through data condensation, data display, and conclusion drawing, while methodological triangulation was applied to ensure trustworthiness. The findings revealed that SRBL effectively supported idea generation by connecting writing tasks with real-world experiences. The use of structured guiding questions provided instructional scaffolding that enabled students to produce more detailed, coherent, and well-organized descriptive texts. Students also reported positive perceptions of the approach, describing it as engaging, practical, and less intimidating than conventional writing instruction. The study concludes that SRBL represents an effective contextualized pedagogical approach for improving EFL descriptive writing. The findings imply that integrating spatial observation and guided descriptive frameworks can enhance writing instruction, particularly in vocational higher education contexts where experiential learning is highly valued.